2012
DOI: 10.1089/ten.tea.2011.0349
|View full text |Cite
|
Sign up to set email alerts
|

Granule Size–Dependent Bone Regenerative Capacity of Octacalcium Phosphate in Collagen Matrix

Abstract: The present study was designed to determine whether the osteoconductivity of octacalcium phosphatecollagen (OCP/Col) composite can be improved by controlling the granule size of OCP. The granules of synthetic OCP, with diameters in the range of 53 to 300, 300 to 500, and 500 to 1000 mm, were used as an inorganic source of composite materials mixed with atelo-Col. After vacuum dehydrothemal treatment, OCP/Col disks were implanted into critical-sized calvaria defects in Wistar rats for 4, 8, and 12 weeks and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…The previous study by OCP implantation in the granule form in mouse calvaria criticalsized defect, which could be a nonloading locus, showed that bone formation became higher with increasing the granule size accompanied by higher appearance of TRAPpositive cells. 38 Similar result was observed in the implantation of OCP/Gel composite in rat calvaria defect. 30 An interesting finding in the present results is that the appearance of osteoclast-like cells was suppressed in OCP/ Gel with PTFE (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The previous study by OCP implantation in the granule form in mouse calvaria criticalsized defect, which could be a nonloading locus, showed that bone formation became higher with increasing the granule size accompanied by higher appearance of TRAPpositive cells. 38 Similar result was observed in the implantation of OCP/Gel composite in rat calvaria defect. 30 An interesting finding in the present results is that the appearance of osteoclast-like cells was suppressed in OCP/ Gel with PTFE (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…3). 14,35,38,[42][43][44] However, because OCP small crystals-co-precipitated gelatin composite induced TRAPpositive cells during bone regeneration in rat calvaria defect, 39 the activity of OCP probably associated with the size of the OCP granules, may be involved in accumulation of the osteoclast-like cells in the present OCP/Gel composites. 11 This may be stemmed from the difference of the matrix materials between gelatin and collagen, in which the appearance of TRAP-positive cells by onlaid Gel sponges was almost inhibited in both the mechanical stress conditions with and without PTFE support (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Two surface species were always formed when hydration equilibrium was reached; deprotonated ( > SCrO 4 ) and protonated (> SHCrO 4 ) complexes, which were more stable in near neutral, than acidic, solution. This was consistent with modeling adsorption data, indicating a mixture of both monodentate and bidentate chromate surface complexes on goethite [62,63].…”
Section: Equilibrium Constantssupporting
confidence: 89%
“…27 After 5 weeks, 60 to 82% of BioCaP degraded ( Figure 6B), which indicated a significantly higher degradability of BioCaP than most of the clinically used CaP-based bone-filling materials. 27 After 5 weeks, 60 to 82% of BioCaP degraded ( Figure 6B), which indicated a significantly higher degradability of BioCaP than most of the clinically used CaP-based bone-filling materials.…”
Section: Discussionmentioning
confidence: 96%